Purr-ogrammed Love: A Narrative Review of Virtual Pets - Dodd, M; Fowler, A; Lottridge, D (Elsevier BV, 2025)
In the ‘90s Tamagotchi (Tamagotchi, 1996) and virtual pets were cultural touchstones of the personal computer and handheld game console revolutions. Despite continued popularity, virtual pets remain under-researched. A narrative review was conducted to identify key themes in the literature surrounding virtual pets. 45 articles were included. Reflexive thematic analysis identified six major themes: life and death, health and habits, capitalism and consumption, gender, toys and play, and ethics. Virtual pets serve purposes beyond entertainment, including managing physical and emotional well-being and aiding in learning. Virtual pet gameplay is also seen to challenge normative notions of productivity and purpose. This review brings together decades of academic interest in virtual pets across disciplines to better understand their enduring cultural significance.
Keywords: 46 Information and Computing Sciences; 4607 Graphics, Augmented Reality and Games; 4608 Human-Centred Computing; 4603 Computer Vision and Multimedia Computation; 0801 Artificial Intelligence and Image Processing; 1902 Film, Television and Digital Media; 2001 Communication and Media Studies; Virtual pets; Cyber pets; Digital pets; Digital ownership; Gendered toys; Capitalist design; Narrative review; Facilitated healthcare